A method for edge sealing of a coated paint performance board
By using two-component epoxy primer or two-component polyurethane medium coating to seal the coating performance board, the problem of unsolid edge sealing in the prior art is solved, and more accurate coating performance testing and more stable long-term performance are achieved.
Patent Information
- Application Number
- CN202011298643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-19
AI Technical Summary
In the prior art, the edge sealing effect of the coating performance board is not strong, resulting in inaccurate coating performance test results, especially in long-term performance tests, the edge sealing is prone to erosion.
Edge sealing is performed using two-component epoxy primer or two-component polyurethane paint, and a firm edge sealing is formed through immersion and drying.
Higher edge sealing and stability are achieved, ensuring the accuracy of coating performance testing and preventing edge erosion in long-term performance testing.
Smart Images

Figure BDA0002786143080000011 
Figure BDA0002786143080000021 
Figure BDA0002786143080000031
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coatings, and more specifically, to a method for edge sealing a coated coating performance board. Background Art
[0002] When testing the mechanical or chemical properties of an automotive coating, it is necessary to prepare the paint film under standard methods and then conduct various tests; however, the edges of the prepared performance boards often do not reach the standard construction film thickness, and some technicians may cut the performance boards into multiple pieces to test more properties. At this time, when testing water resistance, gasoline resistance, and other immersion liquid resistance, moisture and heat resistance, salt spray resistance and other properties, it is necessary to perform edge sealing on the performance boards to prevent the immersion liquid from corroding the paint film from the edges, causing inaccurate test results.
[0003] The existing edge sealing technology usually uses a 1:1 paraffin and rosin mixture for edge sealing or waterproof tape for edge sealing. When doing long-term performance, the above edge sealing methods have the problem of loose sealing; and when the performance board using waterproof tape for edge sealing is tested for gasoline resistance, the tape will fall off. Summary of the invention
[0004] Based on the above problems, the purpose of the present invention is to provide a method for edge sealing of a coated paint performance board. The edge sealing method has good reliability and can accurately obtain the results of various paint performance tests.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for sealing the edges of a coated paint performance board, using a two-component paint to seal the edges of the paint performance board.
[0007] Furthermore, the two-component coating is a two-component epoxy primer or a two-component polyurethane mid-coat.
[0008] Furthermore, in the method, the edge portion of the coated performance board that needs to be sealed is immersed in the two-component coating, then taken out and dried.
[0009] Furthermore, the two-component epoxy primer comprises component A and component B, wherein:
[0010] Calculated by mass percentage of the total mass of component A, component A contains the following ingredients:
[0011]
[0012] Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients:
[0013] Polyamide or phenolic amide 22-50%;
[0014] Silane coupling agent 1-3%;
[0015] Second solvent 49-77%;
[0016] Wherein, the mass ratio of component A to component B is 1.5-9.6:1;
[0017] The ratio of the molar amount of the amine groups in the polyamide or phenolic amide to the molar amount of the epoxy groups in the epoxy resin is 0.85-1.1:1.
[0018] Furthermore, the epoxy equivalent of the bisphenol A epoxy resin is 100-500, preferably 450-500.
[0019] Furthermore, the amine value of the polyamide or phenolic amide is 90-270.
[0020] Furthermore, the first solvent is selected from one or more of alcohol, benzene, ether or ketone solvents.
[0021] Furthermore, the first solvent is selected from one or more of isobutyl alcohol, n-butyl alcohol, xylene, S-100#, ethylene glycol butyl ether, propylene glycol methyl ether, cyclohexanone, and methyl isobutyl ketone.
[0022] Furthermore, the filler is selected from one or more of titanium dioxide, zinc oxide, carbon black, aluminum phosphate, talc, and barium sulfate.
[0023] Furthermore, the second solvent is selected from one or more of alcohol, benzene and ether solvents.
[0024] Furthermore, the second solvent is selected from one or more of isopropyl alcohol, xylene, methyl isobutyl ketone, propylene glycol methyl ether, and ethylene glycol butyl ether.
[0025] Furthermore, the two-component polyurethane mid-coat paint comprises component a and component b, wherein:
[0026] Calculated by mass percentage of the total mass of component a, component a contains the following ingredients:
[0027]
[0028] Calculated by mass percentage of the total mass of the b component, the b component contains the following ingredients:
[0029] HDI or TDI 40-60%;
[0030] The fourth solvent 40-60%;
[0031] Among them, the mass ratio of component a to component b is 3.9-11.6:1.
[0032] Furthermore, the hydroxyl value of the acrylic resin is 50-80 mg KOH / g, preferably 60-75 mg KOH / g.
[0033] Furthermore, the molar ratio of -NCO in the HDI or TDI to -OH in the acrylic resin is 1.0-1.45:1.
[0034] Furthermore, the filler is selected from one or more of titanium dioxide, carbon black, kaolin, talc, calcium carbonate and barium sulfate.
[0035] Furthermore, the third solvent and the fourth solvent are each independently selected from ester or benzene solvents.
[0036] Furthermore, the third solvent and the fourth solvent are independently selected from one or more of butyl acetate, propylene glycol methyl ether acetate, and xylene.
[0037] Furthermore, the coating performance plate is an electrophoresis plate.
[0038] Furthermore, the coating applied on the coating performance board includes water-based primer, water-based color paint, and two-component varnish in sequence.
[0039] Furthermore, the application amount of the two-component coating is 0.03-0.1 g / cm 2 .
[0040] The beneficial effects of the present invention are as follows:
[0041] In the method for edge sealing of the painted paint performance board provided by the present invention, by adopting two-component epoxy primer or two-component polyurethane mid-coat for edge sealing, the problem in the prior art that the paint performance board has inaccurate paint performance testing due to poor edge sealing effect (such as loose edge sealing) is overcome. At the same time, the method can ensure that the edges of the performance board are not corroded when testing long-term performance. DETAILED DESCRIPTION
[0042] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0043] One embodiment of the present invention provides a method for edge sealing of a coated paint performance board, wherein a two-component paint is used to edge seal the paint performance board.
[0044] Specifically, in a preferred example, in the method, the edge portion of the coated paint performance board that needs to be sealed is immersed in the two-component paint, then taken out and dried.
[0045] Furthermore, the two-component coating is preferably a two-component epoxy primer or a two-component polyurethane mid-coat.
[0046] In the edge sealing method of this embodiment, a two-component coating, preferably a two-component epoxy primer or a two-component polyurethane mid-coat, is used as the edge sealing material, which can better overcome the problems of low test result accuracy caused by loose sealing when the existing edge sealing uses a mixture of paraffin and rosin or waterproof tape as an edge sealing material for long-term performance tests of physical or chemical properties of automotive coatings (for example, water resistance, gasoline resistance, various immersion liquids, moisture and heat resistance, salt spray resistance, etc.), and the waterproof tape falls off when testing gasoline resistance, resulting in low test yield and high cost.
[0047] The two-component epoxy primer in this embodiment can be considered to include component A and component B, wherein preferably, based on the mass percentage of the total mass of component A, component A includes the following ingredients:
[0048]
[0049] Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients:
[0050] Polyamide or phenolic amide 22-50%;
[0051] Silane coupling agent 1-3%;
[0052] Second solvent 49-77%.
[0053] When the two-component epoxy primer is used to seal the coating performance board, component A and component B are mixed for edge sealing, and the mass ratio of component A to component B is 1.5-9.6:1; the ratio of the molar amount of amino groups in polyamide or phenolic amide to the molar amount of epoxy groups in epoxy resin is 0.85-1.1:1.
[0054] The above-mentioned two-component epoxy primer is used to seal the edges of the performance boards coated with the coating, which has higher sealing firmness and good sealing. It is suitable for testing various physical and chemical properties such as water resistance, gasoline resistance, various immersion liquids and moisture and heat resistance, salt spray resistance, etc., and the test accuracy is higher.
[0055] In this embodiment, the epoxy equivalent of the bisphenol A epoxy resin may preferably be 100-500, and the bisphenol A epoxy resin in this case has excellent chemical resistance and corrosion resistance. Preferably, the bisphenol A epoxy resin is NPSN-901×75 (epoxy equivalent 450-500) produced by Nan Ya Company.
[0056] The filler in this embodiment (to distinguish from the following, it may also be referred to as the first filler) may preferably include but is not limited to one or more of fillers selected from titanium dioxide, zinc oxide, carbon black, aluminum phosphate, talc, and barium sulfate.
[0057] For example, the anti-settling agent may include, but is not limited to, bentonite, fumed silica, and the like.
[0058] Exemplarily, the amine value of the polyamide or phenolic amide is 90-270. Suitable polyamides in this embodiment include but are not limited to phenolic amides of model NX 2015 (amine value 200) and model LITE 3100 (amine value 260) from Cardolite and polyamides of model SUNMIDE E-1000 (amine value 90-110) from Air Chemicals, all of which have fast drying at room temperature, excellent water resistance and salt spray resistance.
[0059] In this embodiment, the role of the solvent is mainly to dissolve the components. Exemplarily, the first solvent is selected from one or more of alcohols, benzenes, ethers or ketones. More preferably, the first solvent is selected from one or more of isobutyl alcohol, n-butyl alcohol, xylene, S-100#, ethylene glycol butyl ether, propylene glycol methyl ether, cyclohexanone, and methyl isobutyl ketone.
[0060] Exemplarily, the second solvent is selected from one or more of alcohols, benzenes, and ether solvents. More preferably, the second solvent is selected from one or more of isopropyl alcohol, xylene, methyl isobutyl ketone, propylene glycol methyl ether, and ethylene glycol butyl ether.
[0061] Silane coupling agents can be used to increase the crosslinking density. Silane coupling agents suitable for use in this embodiment include, but are not limited to, silane coupling agents of model SE-01-A2 produced by Shin-Etsu Chemical.
[0062] In a preferred example, the two-component polyurethane mid-coat paint comprises component a and component b, wherein:
[0063] Calculated by mass percentage of the total mass of component a, component a includes the following ingredients:
[0064]
[0065] Calculated by mass percentage of the total mass of the b component, the b component contains the following ingredients:
[0066] HDI or TDI 40-60%;
[0067] The fourth solvent is 40-60%.
[0068] When the two-component polyurethane mid-coat is used to seal the edges of the coating performance board, component a and component b are mixed before edge sealing, and the applied amount mass ratio of component a to component b is preferably 3.9-11.6:1.
[0069] Preferably, the hydroxyl value of the acrylic resin suitable for the present embodiment is 50-80 mg KOH / g, preferably 60-75 mg KOH / g. The use of the acrylic resin in this hydroxyl value range allows the two-component epoxy primer to be quickly cured and dried when used for edge sealing, and has excellent pigment wettability and coating construction performance to meet the process requirements of rapid coating. Exemplarily, the acrylic resin can be an acrylic resin with a hydroxyl value of (66±5 mgKOH / g) of ETERAC 7328-ST-50 produced by Changxing Company.
[0070] Preferably, the molar ratio of -NCO in the HDI or TDI to -OH in the acrylic resin is 1.0-1.45: 1. In this case, the resin can be quickly cured and dried, and has good chemical resistance.
[0071] Exemplarily, the filler (which may be referred to as the second filler) is selected from one or more of titanium dioxide, carbon black, kaolin, talc, calcium carbonate, and barium sulfate.
[0072] Preferably, the third solvent and the fourth solvent are each independently selected from ester or benzene solvents. Exemplarily, the third solvent and the fourth solvent are each independently selected from one or more of butyl acetate, propylene glycol methyl ether acetate, and xylene.
[0073] The function of the dispersant is to facilitate wetting and dispersing the pigment. The dispersant suitable for use in this embodiment includes but is not limited to BASF's EFKA-4010 dispersant.
[0074] Exemplarily, the anti-settling agent may be selected from one or more of bentonite and fumed silica.
[0075] For example, the HDI may be CORONATE HXR (NCO content 21.6%-22.1%) HDI from Tosoh Corporation and Desmodur L75 (NCO content 13.3%±0.4%) TDI from Covestro.
[0076] Furthermore, in a preferred example, the application amount of the two-component coating is 0.03-0.1 g / cm 2 By adopting the edge sealing method of the present invention, only a small amount of two-component coating material for edge sealing can be used to make the edge sealing firm.
[0077] In this embodiment, the suitable coating performance board is an electrophoresis board. Before edge sealing, the coatings applied on the coating performance board can be water-based primer, water-based color paint, and two-component varnish in sequence. In this embodiment, there are no special requirements for the composition of the aforementioned water-based primer, water-based color paint, and two-component varnish, and they can be related products publicly used in automotive coatings in the field.
[0078] The technical solution of the present invention is described below in conjunction with some specific embodiments:
[0079] Example 1
[0080] A method for edge sealing of a painted performance board, wherein the edge portion of the painted performance board that needs to be edge sealed is immersed in a two-component epoxy primer, then taken out and placed in a fume hood to prevent the epoxy primer from volatilizing solvents during the drying process to cause personal or environmental harm, and then dried for 24 hours.
[0081] Wherein, in the above two-component epoxy primer, the component A contains the following components, calculated by mass percentage of the total mass of the component A:
[0082]
[0083] The filler is specifically: 13% titanium dioxide, 18% barium sulfate, 12% talc, 10.5% aluminum phosphate, and 0.2% carbon black;
[0084] The first solvent specifically comprises: 10% xylene and 11% isobutanol.
[0085] Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients:
[0086] NX 2015 phenaldehyde amide 22%;
[0087] SE-01-A2 silane coupling agent 1%;
[0088] Second solvent 77%;
[0089] The second solvent specifically comprises 26% xylene and 51% isopropanol.
[0090] The preparation of the above two-component epoxy primer comprises the following steps:
[0091] Preparation of component A: Slowly add the materials in order and disperse them, then use a sand mill or oscillator to grind the fineness to 30 microns.
[0092] Preparation of component B: Slowly add the materials in order and disperse them.
[0093] When the two-component epoxy primer is used for edge sealing, the mixing mass ratio of component A to component B is 3.8:1. When the two-component epoxy primer is used for edge sealing, the application amount of the two-component epoxy primer is 0.05 g / cm 2 .
[0094] Among them, the coating performance board test board is a performance board made on-site by the customer according to the standard paint film preparation conditions (including pre-treatment - cathode electrophoresis + water-based primer B1 + water-based color paint + 2K varnish). Specifically, the coating performance board test board is made of Nippon IPP products, and the conditions are:
[0095] A. Substrate: electrophoresis plate;
[0096] B. Surface treatment: solvent degreasing (acetic acid: toluene = 1:1).
[0097] C. Painting method: 3C1B.
[0098] D. Flashing and baking time: After the B0 intermediate coating flashes off for 8 minutes, continue to spray the B1 color paint, level it for 2 minutes, and then pre-bake it at 80℃*8min; after cooling, spray 2K varnish (2K varnish: curing agent = 3:1) and level it for 8 minutes, and bake it at 145℃ for 28 minutes;
[0099] E. Products: B0 is Nippon PRIMER IPP G2 Medium GREY; B1 is Nippon BASE COAT IPPG2 Diamond Black (JAC); clear coat is Nippon CLEAR COAT 2K HD; curing agent is HARDENER for 2K HD (ratio 3:1)
[0100] F. Film thickness control: B0: 12±2μm; B1: 12±2μm; Varnish: 45±5μm.
[0101] Example 2
[0102] A method for edge sealing of a painted performance board, wherein the edge portion of the painted performance board that needs to be edge sealed is immersed in a two-component epoxy primer, then taken out and placed in a fume hood to prevent the epoxy primer from volatilizing solvents during the drying process to cause personal or environmental harm, and then dried for 24 hours.
[0103] Wherein, in the above two-component epoxy primer, the component A contains the following components, calculated by mass percentage of the total mass of the component A:
[0104]
[0105] The filler is specifically: 20% titanium dioxide, 12% barium sulfate, 10% talc, 8% aluminum phosphate, 4.9% zinc oxide, and 0.1% carbon black;
[0106] The first solvent specifically comprises: 10.6% xylene and 12% isobutanol.
[0107] Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients:
[0108] LITE 3100 Phenalkamide 22%;
[0109] SE-01-A2 silane coupling agent 2%;
[0110] Second solvent 76%;
[0111] The second solvent specifically comprises: 38% xylene and 38% isopropanol.
[0112] The preparation method of the two-component epoxy primer is the same as that of Example 1.
[0113] When the two-component epoxy primer is used for edge sealing, the mixing mass ratio of component A to component B is 4.0:1. When the two-component epoxy primer is used for edge sealing, the application amount of the two-component epoxy primer is 0.07 g / cm 2 .
[0114] Specifically, the coating performance test board is made of Nippon paint water-based 3C2B product, and the conditions are:
[0115] A. Substrate: electrophoresis plate;
[0116] B. Surface treatment: solvent degreasing (acetic acid: toluene = 1:1).
[0117] C. Painting method: 3C2B.
[0118] D. Flashing and baking time: After the intermediate coating flashes off for 3 minutes, pre-bake at 80℃ for 8 minutes, and bake at 145℃*25 minutes; spray the color paint after cooling, pre-bake at 80℃ for 8 minutes after leveling for 2 minutes, spray the water-based matching varnish after cooling, level for 8 minutes, and bake at 145℃*25 minutes;
[0119] E. Products: The midcoat is DWP120W water-based midcoat paint (white); the color paint is AR 2000 water-based metallic paint (shining noble black); the clearcoat is MACO-1880 high weather resistance clearcoat;
[0120] F. Film thickness control: mid-coat: 35±5μm; B1: 15±2μm; clear coat: 35±5μm.
[0121] Example 3
[0122] Same as Example 1, except that:
[0123] In the above two-component epoxy primer, component A contains the following components, calculated by mass percentage of the total mass of component A:
[0124]
[0125] The filler is specifically: 12% titanium dioxide, 18% barium sulfate, 12% talc, 10.3% aluminum phosphate, and 0.2% carbon black;
[0126] The first solvent specifically comprises: 10% xylene and 10% isobutanol.
[0127] Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients:
[0128] SUNMIDE E-1000 polyamide 50%;
[0129] SE-01-A2 silane coupling agent 1%;
[0130] Second solvent 49%;
[0131] The second solvent is specifically: 24% xylene and 25% isopropanol.
[0132] When the two-component epoxy primer is used for edge sealing, the mixing mass ratio of component A to component B is 4.2:1. When the two-component epoxy primer is used for edge sealing, the application amount of the two-component epoxy primer is 0.03 g / cm 2 .
[0133] The other conditions remain unchanged and edge sealing is achieved.
[0134] Example 4
[0135] A method for edge sealing of a painted performance board, wherein the edge portion of the painted performance board that needs to be edge sealed is immersed in a two-component polyurethane mid-coat paint, then taken out and placed in a fume hood to prevent the two-component polyurethane mid-coat paint from evaporating the solvent during the drying process and causing personal or environmental harm, and then dried for 24 hours.
[0136] The above two-component polyurethane mid-coat paint comprises component a and component b, wherein:
[0137] Calculated by mass percentage of the total mass of component a, component a includes the following ingredients:
[0138]
[0139] The fillers are specifically: carbon black 0.1%, titanium dioxide 12%, barium sulfate 12%, calcium carbonate 12%, kaolin 4%, talc 8.9%;
[0140] The third solvent is specifically: 6% xylene and 6% butyl ester.
[0141] Calculated by mass percentage of the total mass of the b component, the b component contains the following ingredients:
[0142] CORONATE HXRHDI 42%;
[0143] The fourth solvent 58%;
[0144] The fourth solvent specifically comprises 27% xylene, 27% butyl acetate and 4% propylene glycol methyl ether acetate.
[0145] The preparation of the above two-component polyurethane mid-coat paint comprises the following steps:
[0146] Preparation of component a: Slowly add the materials in order and disperse them, then use a sand mill or oscillator to grind them to a fineness of 30 microns.
[0147] Preparation of component b: Slowly add the materials in order and disperse them.
[0148] When the above two-component polyurethane mid-coat is used for edge sealing, the mixing mass ratio of component a to component b is 7:1. When edge sealing, the application amount of the two-component polyurethane mid-coat is 0.04g / cm 2 .
[0149] Specifically, the coating performance test board is made of Nippon paint water-based 3C2B product, and the conditions are:
[0150] A. Substrate: electrophoresis plate;
[0151] B. Surface treatment: solvent degreasing (acetic acid: toluene = 1:1).
[0152] C. Painting method: 3C2B.
[0153] D. Flashing and baking time: After the intermediate coating flashes off for 3 minutes, pre-bake at 80℃ for 8 minutes, and bake at 145℃*25 minutes; spray the color paint after cooling, pre-bake at 80℃ for 8 minutes after leveling for 2 minutes, spray the water-based matching varnish after cooling, level for 8 minutes, and bake at 145℃*25 minutes;
[0154] E. Products: The midcoat is DWP120W water-based midcoat paint (white); the color paint is AR 2000 water-based metallic paint (shining noble black); the clearcoat is MACO-1880 high weather resistance clearcoat;
[0155] F. Film thickness control: mid-coat: 35±5μm; B1: 15±2μm; clear coat: 35±5μm.
[0156] Example 5
[0157] A method for edge sealing of a painted performance board, wherein the edge portion of the painted performance board that needs to be edge sealed is immersed in a two-component polyurethane mid-coat paint, then taken out and placed in a fume hood to prevent the two-component polyurethane mid-coat paint from evaporating the solvent during the drying process and causing personal or environmental harm, and then dried for 24 hours.
[0158] The above two-component polyurethane mid-coat paint comprises component a and component b, wherein:
[0159] Calculated by mass percentage of the total mass of component a, component a includes the following ingredients:
[0160]
[0161] The fillers are specifically: carbon black 0.2%, titanium dioxide 14%, barium sulfate 13%, calcium carbonate 9%, kaolin 8%, talc 10.8%;
[0162] The third solvent is specifically: 3% propylene glycol encrypted acetate, 4% xylene, and 4% butyl acetate.
[0163] Calculated by mass percentage of the total mass of the b component, the b component contains the following ingredients:
[0164] Desmodur L75TDI 40%;
[0165] The fourth solvent 60%;
[0166] The fourth solvent specifically comprises 30% xylene and 30% butyl ester.
[0167] The preparation of the above two-component polyurethane mid-coat is the same as in Example 4.
[0168] When the above two-component polyurethane intermediate coating is used for edge sealing, the mixing mass ratio of component a to component b is 4.8:1. When sealing the edge, the application amount of the two-component polyurethane intermediate coating is 0.08g / cm 2 .
[0169] Specifically, the coating performance test board is made of Nippon paint water-based 3C2B product, and the conditions are:
[0170] A. Substrate: electrophoresis plate;
[0171] B. Surface treatment: solvent degreasing (acetic acid: toluene = 1:1).
[0172] C. Painting method: 3C2B.
[0173] D. Flashing and baking time: After the intermediate coating flashes off for 3 minutes, pre-bake at 80℃ for 8 minutes, and bake at 145℃*25 minutes; spray the color paint after cooling, pre-bake at 80℃ for 8 minutes after leveling for 2 minutes, spray the water-based matching varnish after cooling, level for 8 minutes, and bake at 145℃*25 minutes;
[0174] E. Products: The midcoat is DWP120W water-based midcoat paint (white); the color paint is AR 2000 water-based metallic paint (shining noble black); the clearcoat is MACO-1880 high weather resistance clearcoat;
[0175] F. Film thickness control: mid-coat: 35±5μm; B1: 15±2μm; clear coat: 35±5μm.
[0176] Among them, the coating performance test board is made of Nippon IPP product board, the conditions are:
[0177] A. Substrate: electrophoresis plate;
[0178] B. Surface treatment: solvent degreasing (acetic acid: toluene = 1:1).
[0179] C. Painting method: 3C1B.
[0180] D. Flashing and baking time: After the B0 intermediate coating flashes off for 8 minutes, continue to spray the B1 color paint, level it for 2 minutes, and then pre-bake it at 80℃*8min; after cooling, spray 2K varnish (2K varnish: curing agent = 3:1) and level it for 8 minutes, and bake it at 145℃ for 28 minutes;
[0181] E. Products: B0 is Nippon PRIMER IPP G2 Medium GREY; B1 is Nippon BASE COAT IPPG2 Diamond Black (JAC); clear coat is Nippon CLEAR COAT 2K HD; curing agent is HARDENER for 2K HD (ratio 3:1)
[0182] F. Film thickness control: B0: 12±2μm; B1: 12±2μm; Varnish: 45±5μm.
[0183] Example 6
[0184] Same as Example 4, except that:
[0185] The above two-component polyurethane mid-coat paint comprises component a and component b, wherein:
[0186] Calculated by mass percentage of the total mass of component a, component a includes the following ingredients:
[0187]
[0188] The fillers are specifically: carbon black 0.2%, titanium dioxide 13%, barium sulfate 11%, calcium carbonate 9%, kaolin 8%, talc 10.8%;
[0189] The third solvent is specifically: 3% propylene glycol encrypted acetate, 4.5% xylene, and 4.6% butyl acetate.
[0190] Calculated by mass percentage of the total mass of the b component, the b component contains the following ingredients:
[0191] CORONATE HXRHDI 45%;
[0192] The fourth solvent 55%;
[0193] The fourth solvent is specifically: 25% xylene and 25% butyl ester.
[0194] The preparation of the above two-component polyurethane mid-coat is the same as in Example 4.
[0195] When the above two-component polyurethane intermediate coating is used for edge sealing, the mixing mass ratio of component a to component b is 7.2:1. When sealing the edge, the application amount of the two-component polyurethane intermediate coating is 0.05g / cm 2 .
[0196] The other conditions remain unchanged and edge sealing is achieved.
[0197] Comparative Example 1
[0198] Example 1 was repeated, except that the phenolic acid amide in the component B of Example 1 was replaced with a phenolic acid amide having an amine value of 50, and other conditions remained unchanged to complete the edge sealing. During the edge sealing drying process, it could not be completely dried within 24 hours.
[0199] Comparative Example 2
[0200] Example 1 was repeated, except that when the two-component epoxy primer was used for edge sealing, the mixing mass ratio of component A to component B was 1.2:1.
[0201] Comparative Example 3
[0202] Example 1 was repeated, except that when the two-component epoxy primer was used for edge sealing, the mixing mass ratio of component A to component B was 10:1.
[0203] Comparative Example 4
[0204] Example 4 was repeated, except that the acrylic resin in Example 4 was replaced with an acrylic resin having a hydroxyl value of 40 mg KOH / g, and other conditions remained unchanged. The paint film could not be completely cured after 24 hours, resulting in poor chemical resistance after edge sealing.
[0205] Comparative Example 5
[0206] Example 4 was repeated, except that the acrylic resin in Example 4 was replaced with an acrylic resin with a hydroxyl value of 140 mg KOH / g, and other conditions remained unchanged to complete edge sealing. In this case, there would be residual -OH in the acrylic acid that did not participate in the reaction, resulting in poor chemical resistance of the paint film.
[0207] Comparative Example 6
[0208] The Nippon paint IPP product board mentioned in Example 1 was edge-sealed using 3M waterproof tape.
[0209] Performance Test:
[0210] The test panels obtained from each embodiment and comparative example were tested:
[0211] 1. Gasoline resistance test:
[0212] Method: GB / T 1734;
[0213] Experimental results:
[0214] After the gasoline resistance test was performed using the methods of the embodiments of the present application, the visual appearance of the paint film of the test plate had no wrinkles, bubbles or any variation, and the adhesion was grade 0.
[0215] Comparative Example 1: After the gasoline resistance test was conducted using the edge sealing method of Comparative Example 1, the paint film of the test panel had slight wrinkles on its visual appearance, and the adhesion was level 1.
[0216] Comparative Example 2: After the gasoline resistance test was conducted using the edge sealing method of Comparative Example 2, the paint film of the test panel had slight wrinkles on its visual appearance, and the adhesion was level 0.
[0217] Comparative Example 3: After the gasoline resistance test was conducted using the edge sealing method of Comparative Example 3, the paint film of the test panel had slight wrinkles on its visual appearance, and the adhesion was level 0.
[0218] Comparative Example 4: After the gasoline resistance test was conducted using the edge sealing method of Comparative Example 4, the paint film of the test panel had slight wrinkles on its visual appearance, and the adhesion was level 0.
[0219] Comparative Example 5: After the gasoline resistance test was conducted using the edge sealing method of Comparative Example 5, the paint film of the test panel had slight wrinkles on its visual appearance, and the adhesion was level 1.
[0220] Comparative Example 6: After the gasoline resistance test using the waterproof tape to seal the edges, the paint film of the test panel showed obvious wrinkles, and the adhesion was level 2.
[0221] 2. Water resistance test:
[0222] Method: GB / T 5209.
[0223] Experimental results:
[0224] After the water resistance test using the methods of the embodiments of the present application, the visual appearance of the paint film of the test plate has no wrinkles, bubbles or any variation, and the adhesion is level 0.
[0225] Comparative Example 1: After the water resistance test was performed using the edge sealing method of Comparative Example 1, the paint film of the test plate visually showed slight bubbling and wrinkling on the appearance, and the adhesion was level 1.
[0226] Comparative Example 2: After the water resistance test was performed using the edge sealing method of Comparative Example 2, the visual appearance of the paint film of the test plate had no bubbles or slight wrinkles, and the adhesion was level 0.
[0227] Comparative Example 3: After the water resistance test was performed using the edge sealing method of Comparative Example 3, the visual appearance of the paint film of the test panel showed no bubbles or slight wrinkles, and the adhesion was level 0.
[0228] Comparative Example 4: After the water resistance test was performed using the edge sealing method of Comparative Example 4, the paint film of the test plate visually showed slight bubbling and wrinkling on the appearance, and the adhesion was level 0.
[0229] Comparative Example 5: After the water resistance test was performed using the edge sealing method of Comparative Example 5, the visual appearance of the paint film of the test plate showed slight bubbling and wrinkling, and the adhesion was level 1.
[0230] Comparative Example 6: After the water resistance test using the waterproof tape to seal the edges, the paint film of the test panel visually showed slight bubbling and wrinkling, and the adhesion was level 1.
[0231] 3. Moisture and heat resistance test:
[0232] Method: Great Wall Enterprise Standard Q / CC SY257-2012.
[0233] Experimental results: After the moisture and heat resistance test was performed using the methods of the embodiments of the present application, the visual appearance of the paint film of the test panel showed no cracking, peeling, etc., no obvious change in appearance, and the adhesion was level 0.
[0234] Comparative Example 1: After the moisture and heat resistance test was conducted using the edge sealing method of Comparative Example 1, the visual appearance of the paint film on the test plate showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0235] Comparative Example 2: After the moisture and heat resistance test was conducted using the edge sealing method of Comparative Example 2, the visual appearance of the paint film on the test plate showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0236] Comparative Example 3: After the moisture and heat resistance test was conducted using the edge sealing method of Comparative Example 3, the visual appearance of the paint film on the test board showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0237] Comparative Example 4: After the moisture and heat resistance test was conducted using the edge sealing method of Comparative Example 4, the visual appearance of the paint film of the test panel showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0238] Comparative Example 5: After the moisture and heat resistance test was conducted using the edge sealing method of Comparative Example 5, the visual appearance of the paint film on the test board showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0239] Comparative Example 6: After the moisture and heat resistance test was conducted using the tape edge sealing method, the visual appearance of the paint film on the test panel showed no cracking, peeling, etc., the paint film was slightly wrinkled, and the adhesion was level 0.
[0240] 4. Acid discoloration resistance test:
[0241] Method: Jinbei enterprise standard HI-J04.04.029-2010-1.0.
[0242] Experimental results:
[0243] After the acid discoloration resistance test was performed using the methods of the embodiments of the present application, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference was:
[0244] Example 1 Color difference ΔE=0.3;
[0245] Example 2 Color difference ΔE=0.33;
[0246] Example 3 color difference ΔE=0.31;
[0247] Example 4 Color difference ΔE=0.34;
[0248] Example 5 Color difference ΔE=0.32;
[0249] Example 6: Color difference ΔE=0.31.
[0250] Comparative Example 1: After the acid discoloration resistance test was conducted using the edge sealing method of Comparative Example 1, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference ΔE=0.42.
[0251] Comparative Example 2: After the acid discoloration resistance test was conducted using the edge sealing method of Comparative Example 2, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference ΔE=0.41.
[0252] Comparative Example 3: After the acid discoloration resistance test was conducted using the edge sealing method of Comparative Example 1, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference ΔE=0.43.
[0253] Comparative Example 4: After the acid discoloration resistance test was conducted using the edge sealing method of Comparative Example 4, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference ΔE=0.39.
[0254] Comparative Example 5: After the acid discoloration resistance test was conducted using the edge sealing method of Comparative Example 5, the visual appearance of the paint film of the test plate had no obvious spots, and the color difference ΔE=0.51.
[0255] Comparative Example 6: After the acid discoloration resistance test using the tape edge sealing method, the paint film appearance of the test plate had no obvious spots, and the color difference ΔE=0.35.
[0256] 5. Windshield washer fluid and antifreeze test:
[0257] Method: Great Wall Enterprise Standard Q / CC SY096-2010.
[0258] Experimental results:
[0259] After the windshield washer fluid and antifreeze fluid resistance tests were performed using the methods of the embodiments of the present application, there was no obvious color change in visual comparison of the test panels, and the adhesion was level 0.
[0260] Comparative Example 1: The test panel subjected to the windshield washer fluid and antifreeze fluid resistance test using the edge sealing method of Comparative Example 1 showed slight visual discoloration, and the adhesion was level 0.
[0261] Comparative Example 2: The test panel subjected to the windshield cleaning fluid and antifreeze fluid resistance test using the edge sealing method of Comparative Example 2 showed very slight visual discoloration, and the adhesion was level 0.
[0262] Comparative Example 3: After the test panel was tested for windshield cleaning fluid and antifreeze fluid resistance using the edge sealing method of Comparative Example 3, it was visually very slightly discolored, and the adhesion was level 0.
[0263] Comparative Example 4: The test panel subjected to the windshield cleaning fluid and antifreeze fluid resistance test using the edge sealing method of Comparative Example 4 showed slight visual discoloration, and the adhesion was level 0.
[0264] Comparative Example 5: The test panel subjected to the windshield cleaning fluid and antifreeze fluid resistance test using the edge sealing method of Comparative Example 5 showed slight visual discoloration, and the adhesion was level 0.
[0265] Comparative Example 6: After the windshield washer fluid and antifreeze fluid resistance test using the tape edge sealing method, the test panel visually changed color slightly, and the adhesion was level 0.
[0266] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for edge sealing a coated performance board, characterized in that: The coating performance board is edge-sealed using a two-component coating; Before edge sealing, the coatings applied on the coating performance board sequentially include water-based primer, water-based color paint, and two-component varnish; The two-component coating is a two-component epoxy primer or a two-component polyurethane mid-coat; In the method, the edge portion of the coated performance board that needs to be sealed is immersed in the two-component coating, then taken out and dried; The two-component epoxy primer comprises component A and component B, wherein: Calculated by mass percentage of the total mass of component A, component A contains the following ingredients: Bisphenol A epoxy resin 22-28%; Anti-settling agent 0.1-0.5%; Filler 50-55%; First solvent 18-24%; Calculated by mass percentage of the total mass of the B component, the B component contains the following ingredients: Polyamide or phenolic amide 22-50%; Silane coupling agent 1-3%; Second solvent 49-77%; Wherein, the mass ratio of component A to component B is 1.5-9.6:1; The ratio of the molar amount of the amine groups in the polyamide or phenolic amide to the molar amount of the epoxy groups in the epoxy resin is 0.85-1.1:1; The amine value of the polyamide or phenalkamide is 90-270; The two-component polyurethane mid-coat paint consists of component a and component b, wherein: Calculated by mass percentage of the total mass of the a component, the a component consists of the following ingredients: Acrylic resin 33-40%; Dispersant 0.3-0.7%; Filler 45-55%; Anti-settling agent 0.1-0.5%; The third solvent 10-20%; Calculated by mass percentage of the total mass of the b component, the b component consists of the following ingredients: HDI or TDI 40-60%; The fourth solvent is 40-60%; Wherein, the mass ratio of component a to component b is 3.9-11.6:1; The acrylic resin has a hydroxyl value of 50-80 mg KOH / g.
2. The method according to claim 1, characterized in that The epoxy equivalent of the bisphenol A epoxy resin is 100-500.
3. The method according to claim 1, characterized in that The epoxy equivalent of the bisphenol A epoxy resin is 450-500.
4. The method according to claim 1, characterized in that The first solvent is selected from one or more of alcohol, benzene, ether or ketone solvents.
5. The method according to claim 1, characterized in that The first solvent is selected from one or more of isobutyl alcohol, n-butyl alcohol, xylene, S-100#, ethylene glycol butyl ether, propylene glycol methyl ether, cyclohexanone, and methyl isobutyl ketone.
6. The method according to claim 1, characterized in that In the two-component polyurethane mid-coat paint, the filler is selected from one or more of titanium dioxide, zinc oxide, carbon black, aluminum phosphate, talcum powder, and barium sulfate.
7. The method according to claim 1, characterized in that The second solvent is selected from one or more of alcohol, benzene and ether solvents.
8. The method according to claim 1, characterized in that The second solvent is selected from one or more of isopropyl alcohol, xylene, methyl isobutyl ketone, propylene glycol methyl ether, and ethylene glycol butyl ether.
9. The method according to claim 1, characterized in that: The acrylic resin has a hydroxyl value of 60-75 mg KOH / g.
10. The method according to claim 1, characterized in that The molar ratio of -NCO in the HDI or TDI to -OH in the acrylic resin is 1.0-1.45:
1.
11. The method according to claim 1, characterized in that: In the two-component polyurethane mid-coat paint, the filler is selected from one or more of titanium dioxide, carbon black, kaolin, talcum powder, calcium carbonate and barium sulfate.
12. The method according to claim 1, characterized in that The third solvent and the fourth solvent are each independently selected from ester or benzene solvents.
13. The method according to claim 1, characterized in that The third solvent and the fourth solvent are independently selected from one or more of butyl acetate, propylene glycol methyl ether acetate and xylene.
14. The method according to claim 1, characterized in that The coating performance plate is an electrophoresis plate.
15. The method according to claim 1, characterized in that The application amount of the two-component coating is 0.03-0.1 g / cm 2 .
Citation Information
Patent Citations
Chromium-free environment-friendly epoxy anticorrosion primer
CN101792285A
Two-component polyurethane coating used for automobile and preparation method thereof
CN102010652A
Method for sealing edges of panel and edge-sealed structure for panel
CN102416812A